2004
DOI: 10.3354/meps272141
|View full text |Cite
|
Sign up to set email alerts
|

Natural hybridization between genetically differentiated populations of Crassostrea gigas and C. angulata highlighted by sequence variation in flanking regions of a microsatellite locus

Abstract: The marine environment is of special interest for studying hybridization between closely related taxa because of the high dispersal potential of planktonic larvae, such as those of most bivalve species. The oysters Crassostrea angulata and C. gigas are known to be very close genetically and entirely inter-fertile under controlled conditions. However, hybridization in the wild had not been investigated, mainly due to the lack of nuclear diagnostic markers. In the present paper, we first estimated genetic differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 55 publications
3
39
0
1
Order By: Relevance
“…Although a number of oyster breeders have conducted interspecific hybridization among the Crassostrea genus Batista et al, 2007Batista et al, , 2008Gaffney and Allen, 1993;Huo et al, 2013;Huvet et al, 2002Huvet et al, , 2004Piferrer et al, 2009;Xu et al, 2009Xu et al, , 2014Zhang et al, 2012Zhang et al, , 2014, there are no reports of further utilization of the hybrids with the exception of two subspecies of C. gigas and C. angulata (Wang et al, 2008). This is the first report to describe completely fertile backcrossed progeny and F 2 hybrids; this finding differed from the F 1 hybrids (C. hongkongensis ♀ × C. gigas ♂) that exhibited high levels of sterility .…”
Section: Restoration Of Progeny Fertilitymentioning
confidence: 74%
“…Although a number of oyster breeders have conducted interspecific hybridization among the Crassostrea genus Batista et al, 2007Batista et al, , 2008Gaffney and Allen, 1993;Huo et al, 2013;Huvet et al, 2002Huvet et al, , 2004Piferrer et al, 2009;Xu et al, 2009Xu et al, , 2014Zhang et al, 2012Zhang et al, , 2014, there are no reports of further utilization of the hybrids with the exception of two subspecies of C. gigas and C. angulata (Wang et al, 2008). This is the first report to describe completely fertile backcrossed progeny and F 2 hybrids; this finding differed from the F 1 hybrids (C. hongkongensis ♀ × C. gigas ♂) that exhibited high levels of sterility .…”
Section: Restoration Of Progeny Fertilitymentioning
confidence: 74%
“…Huvet et al (2004) reported hybridization between introduced Crassostrea gigas (Thunberg, 1793) and the Portuguese oyster C. angulata (Lamarck, 1819), with dramatic consequences for the latter species. Another example occurs in the genus Mytilus in North America.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the production of F1 hybrids between C. angulata and C. gigas under experimental conditions (Imai and Sakai 1961;Menzel 1974;Huvet et al 2002;Batista et al 2007). Hybrids between C. angulata and C. gigas have also been reported in the wild (Huvet et al 2004) and first generation hybrids were shown to be fully viable and fertile under experimental conditions . However, several phenotypic and genetic differences were also reported between C. angulata and C. gigas (for review see Batista et al 2009).…”
Section: Introductionmentioning
confidence: 99%